The Temporality of Barra da Tijuca: Notions of Past, Present and Future in the Mass-Media Narrative about the Neighborhood - Balthazar, Ana Carolina Barreto (2020)
The paper investigates the notions of past, present and future presented by the newspaper O Globo to broadcast the urban expansion of the city of Rio de Janeiro towards the area of Barra da Tijuca in the 1960s and1970s. It focuses on the use of words such as “progress”. Such progress, nevertheless, intends to connect people back to the natural past of Rio: Barra da Tijuca emerges as a new way to live, which avoids the contamination of nature that took place in the neighborhood of Copacabana. The paper then argues that such model of urbanization combined with the logic of mass-media produces a narrative that ignores historical change.